Rituals and Habitus in the Ancient World. An Introduction - Begemann, Elisabeth; Rieger, Anna-Katharina; Rüpke, Jörg; Spickermann, Wolfgang; Waldner, Katharina (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Introduction